Redefining Rhipicephalus sanguineus (sensu lato) species complex in Greece focusing on the mitogenome of Rhipicephalus secundus - Panagiota Ligda; Jan Šlapeta; Anastasios Saratsis; Vaia Kantzoura; Jaisy Chong; Smaragda Sotiraki (Current Research in Parasitology and Vector-Borne Diseases)
Rhipicephalus sanguineus species complex, referred to as R. sanguineus (sensu lato), is distributed globally with some species distributed in specific regions and others spread globally. In Greece, R. sanguineus (s.l.) in dogs, and Rhipicephalus turanicus and Rhipicephalus bursa in livestock, have been repeatedly reported however only based on morphological identification. Recently, there has been a great effort to accurately identify the species belonging to the R. sanguineus species complex, using modern molecular tools and describe their spatial distribution. The aim of this study was to expand the studies on the molecular characterisation of species of the R. sanguineus (s.l.) complex in the Mediterranean region, by molecularly characterising ticks collected from various locations and host species in Greece. Results confirm the presence of Rhipicephalus rutilus, Rhipicephalus secundus, R. bursa, and R. turanicus. The complete mitochondrial genome of R. secundus (approx. 15 kb) from sheep (n = 3) in Greece was sequenced and matched to sequences and morphological data from the type-material from Israel. Additionally, the mitogenome of R. bursa from goats (n = 2) in Greece was sequenced. This study provides a molecular reference for R. secundus, a tick species distributed in the Eastern Mediterranean region.